The Influence Of Organizational Management And Athlete Coaching On The Achievements Of Badminton Athletes - Roy Try Putra; Titin Kuntum Mandalawati (Sekolah Tinggi Olahraga & Kesehatan Bina Guna, 2024)
This study examines the effect of organizational management and athlete coaching on the achievements of East Java Badminton athletes. This study uses primary data in the form of a questionnaire given to respondents with a total of 87 East Java Province Badminton athletes using the simple random sampling method. Based on the results of the study, there is an effect of Organizational Management on the Achievement of East Java Badminton Athletes because the sig t value of the Organizational Management variable is 0.005 < α = 0.05 and tcount> ttable (2.853> 1.198). There is an effect of Athlete Development on the Achievement of East Java Badminton Athletes because the sig value of the Athlete Development variable is 0.002 < α = 0.05 and tcount> t table (3.198 > 1.198). There is an effect of Organizational Management and Athlete Coaching simultaneously on the achievements of East Java Badminton athletes because sig F of 0.000 <0.05 and Fcount of 52.255 is greater than Ftable of 3.95 (39.722> 3.95).